Analysis of the Implementation of the Kurikulum Merdeka in Physics Subject Class XI SMAN 13 Semarang - Lutfita Mukharovatun Azizah; Ani Rusilowati; Bambang Subali (Physics Communication, 2025)
The independent curriculum is an offer to reconstruct the education system freely in accordance with existing resources as the goal of change and progress of the nation in order to adapt to the challenges of globalization. This study aims to find out the difficulties of educators and students in implementing the independent curriculum in Physics learning. The type of descriptive research with a qualitative approach, purposive sampling so that 3 educators from the fields of physics, chemistry, and biology were obtained, as well as 36 students of class XI phase F1 (Physics Specialization) SMAN 13 Semarang. Questionnaire research instruments with Likert scale, interview guidelines and observations. The analysis procedure of this study uses the Miles and Huberman version, the student questionnaire is analyzed using a percentage calculation based on a predetermined category, the interview data is concluded in the analysis of conformity with observation data. The results of the study show that SMAN 13 Semarang is feasible to implement the independent curriculum, facilities and infrastructure can support learning with the implementation of the independent curriculum well. However, educators experience difficulties in several parts of the learning process, namely in  the preparation of the administration of the Independent curriculum such as teaching modules, P5 programs, IT-based learning media and coordinating time during learning. The difficulties also experienced by students of class XI phase F1 in the implementation of the independent learning curriculum of physics learning at SMAN 13 Semarang from the learning implementation factor of 41.7%, the difficulty in understanding physics learning got a percentage of 66.67%, which means that it is quite agreeable to the difficulty of learning physics. The difficulty of learning physics is seen from the learning process where students think that educators are less varied in terms of learning methods 25%, educators are less creative 36.11%.